Assessment of Information Tools: Behavior of Students at Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The most significant function in our daily lives is played by information. Libraries are one of theplaces where students visit when they need to get some information sources to satisfy theirinterests. For their academic work, students mostly rely on books, journals, and databases.Despite being aware of the value and accessibility of visiting a library to conduct research,students or information seekers can encounter several difficulties. The majority of the issuesrevolve around people being unable to obtain the information they require in the shortestpossible time. When a researcher needs more information to study or make judgments, theyparticipate in information-seeking activities. The study's goal was to identify the informationsources utilized by the students in the Bestlink College of the Philippines.The study has revealed that most students prefer to use the Internet for their academic work,assignments, and coursework, for it is easier and more accessible for them than visiting alibrary, which might consume a lot of their time. But browsing the internet still can’t satisfy theirneeds; students still need the collections from the library.Researchers recommend providing internet access, improving library collection andutilization, making information sources available online, conducting a seminar or orientationfor students on how to use OPAC and DDC, and seeking assistance from librarians.
Keywords: Social Sciences